Absorbable silk fibroin medical hemostatic sponge and preparation method thereof
Patent Information
- Application Number
- CN202610694403.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-05-20
AI Technical Summary
[0010]该制备方法整个制备过程无需添加任何化学试剂、工艺简单,易于产业化,解决了现有技术所涉及的化学试剂使用和残留、降解慢、需二次移除的问题
[0022]1. 本发明提出了一种可吸收丝素蛋白医用止血海绵的制备方法,通过将第一分子量丝素蛋白溶液与第二分子量丝素蛋白溶液按比例共混,并将共混溶液先进行冷冻,再在高于冷冻温度且低于0℃的条件下进行升温陈化处理,使丝素蛋白结构转变形成稳定的silk I结构;即,该方法通过晶型调控和分子量配比共同作用优化丝素蛋白止血海绵的力学性能,并赋予止血海绵可快速降解的性能,实现止血海绵在体内1周内降解。
Smart Images

Figure CN122230093B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hemostatic material preparation technology, specifically to an absorbable silk fibroin medical hemostatic sponge and its preparation method. Background Technology
[0002] Traditional absorbable hemostatic materials, such as gelatin sponges and oxidized cellulose, are widely used, but they degrade slowly, cause significant inflammatory reactions, increase patient suffering and infection risk, and their degradation products may cause problems such as inflammatory reactions or foreign body residue.
[0003] Patent publication number CN109091699A discloses a method for preparing a hemostatic sponge. This method uses oxidized cellulose as a raw material, making the hemostatic sponge biodegradable. However, its preparation process is complex, requiring multiple freeze-thaw cycles to obtain the hemostatic sponge precursor, and the in vivo degradation period may take nearly two weeks.
[0004] Ideally, the degradation products of absorbable hemostatic sponges should be components that can be absorbed and metabolized by the human body, and should be non-toxic and non-irritating. Furthermore, their degradation cycle should allow them to be absorbed quickly after achieving hemostasis without requiring a second surgery.
[0005] Silk fibroin, as a natural protein material, possesses excellent biocompatibility, biodegradability, and ease of processing. As a natural protein, silk fibroin can be degraded into peptides and amino acids in the body, allowing for metabolism and absorption. Currently, most common silk fibroin sponges are prepared through cross-linking with chemical cross-linking agents, or by inducing a stable Silk II structure through methanol, ethanol treatment, or high-temperature steam annealing.
[0006] For example, patent CN120285272A discloses a silk fibroin hemostatic sponge loaded with polyhydroxyphenolic compounds and its preparation method. During the preparation process, an organic solvent is used to induce a structural transformation in the silk fibroin, and loading it with polyhydroxyphenolic compounds imparts excellent hemostatic properties. However, this hemostatic sponge has a degradation period of 30 days, which is long and may require postoperative removal.
[0007] Current technology cannot achieve the desired hemostatic performance, good mechanical properties, and rapid degradation within one week.
[0008] Therefore, developing a silk fibroin hemostatic material that does not require chemical cross-linking, possesses excellent hemostatic properties and mechanical properties that meet the requirements of surgical procedures, and can be rapidly and completely absorbed and degraded in vivo, has significant clinical significance and application value. Summary of the Invention
[0009] In view of the technical problems existing in the background art, the present invention provides an absorbable silk fibroin medical hemostatic sponge and its preparation method. The method involves blending a first molecular weight silk fibroin solution and a second molecular weight silk fibroin solution in a certain proportion, freezing the blended solution first, and then aging it at a temperature higher than the freezing temperature but lower than 0°C to transform the silk fibroin structure and form a stable silk I structure. That is, this method optimizes the mechanical properties of the silk fibroin hemostatic sponge through the combined effect of crystal form regulation and molecular weight ratio, and endows the hemostatic sponge with rapid degradability, enabling the hemostatic sponge to degrade within one week in vivo.
[0010] The preparation method requires no chemical reagents during the entire preparation process, is simple, and is easy to industrialize. It solves the problems of chemical reagent use and residue, slow degradation, and the need for secondary removal involved in existing technologies.
[0011] This invention provides a method for preparing absorbable silk fibroin medical hemostatic sponge, comprising the following steps:
[0012] S1, a first molecular weight silk fibroin solution and a second molecular weight silk fibroin solution are mixed in a certain proportion and then frozen; wherein, the volume ratio of the first molecular weight silk fibroin solution to the second molecular weight silk fibroin solution is (1-4):1; the weight average molecular weight of the first molecular weight silk fibroin solution is 250-500 kDa, and the weight average molecular weight of the second molecular weight silk fibroin solution is 50-200 kDa.
[0013] S2, the frozen sample obtained in step S1 is placed under conditions higher than freezing temperature but lower than 0°C for heating and aging treatment, so that the silk fibroin structure is transformed into a stable silk I structure; then the obtained frozen body is freeze-dried to obtain absorbable silk fibroin medical hemostatic sponge.
[0014] Further, in step S1, the mass fraction of both the first molecular weight silk fibroin solution and the second molecular weight silk fibroin solution is 4~8wt%.
[0015] Furthermore, in step S2, the temperature of the heating and aging treatment is -15℃ to 0℃, excluding 0℃.
[0016] Furthermore, in step S2, the heating and aging process takes 12-96 hours.
[0017] Furthermore, in step S1, the freezing temperature is -10℃ to -196℃.
[0018] Furthermore, in step S1, the freezing temperature is -40℃ to -80℃.
[0019] Furthermore, the freeze-drying refers to vacuum drying at -50°C for 35-72 hours.
[0020] The present invention also provides an absorbable silk fibroin medical hemostatic sponge, which is prepared by any of the aforementioned technical solutions using the preparation method described in the preceding technical solutions; the absorbable silk fibroin medical hemostatic sponge is a hemostatic sponge with a silk I structure, which can be autonomously and rapidly absorbed in vivo, and the hemostatic sponge can be degraded in vivo within 1 week.
[0021] The beneficial effects of this invention are as follows:
[0022] 1. This invention proposes a method for preparing absorbable silk fibroin medical hemostatic sponge. The method involves blending a first molecular weight silk fibroin solution with a second molecular weight silk fibroin solution in a specific ratio, freezing the blended solution, and then aging it at a temperature above freezing but below 0°C to transform the silk fibroin structure into a stable silk I structure. In other words, this method optimizes the mechanical properties of the silk fibroin hemostatic sponge through the combined effects of crystal form regulation and molecular weight ratio, and endows the hemostatic sponge with rapid degradability, enabling it to degrade within one week in vivo.
[0023] 2. Traditional hemostatic sponges need to be removed postoperatively and are prone to leaving residues; the absorbable silk fibroin medical hemostatic sponge prepared in this invention can be completely and rapidly absorbed in the body within 1 week, degraded into peptides and amino acids, and completely metabolized.
[0024] 3. This invention is based on the preparation of hemostatic sponges using an aqueous solution system. The entire preparation process is carried out under mild reaction conditions and requires no other chemical reagents.
[0025] 4. The preparation method of the present invention is simple and has a short preparation process. It can prepare hemostatic sponges without special equipment and complicated processes, and solves the problems of chemical reagent use and residue, slow degradation, and the need for secondary removal involved in the prior art.
[0026] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, and in order to make the above and other objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described below. Attached Figure Description
[0027] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the present invention will be briefly described below. Obviously, the drawings described below are merely some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without any creative effort.
[0028] Figure 1 This is a gel permeation chromatogram of the silk fibroin solution used in Example 1.
[0029] Figure 2 The image shows a scanning electron microscope image of the absorbable silk fibroin medical hemostatic sponge prepared in Example 1.
[0030] Figure 3 The image shows a scanning electron microscope (SEM) image of the silk fibroin hemostatic sponge prepared in Comparative Example 1.
[0031] Figure 4 The image shows a scanning electron microscope (SEM) image of the silk fibroin hemostatic sponge prepared in Comparative Example 2.
[0032] Figure 5 The image shows a scanning electron microscope (SEM) image of the silk fibroin hemostatic sponge prepared in Comparative Example 3.
[0033] Figure 6 The images show the XRD patterns of the silk fibroin hemostatic sponges prepared in Example 1 and Comparative Example 3.
[0034] Figure 7 Optical images of the silk fibroin hemostatic sponges prepared in Examples 1-3 and Comparative Examples 1-2.
[0035] Figure 8 The dry compressibility of the silk fibroin hemostatic sponges prepared in Examples 1-3 and Comparative Examples 1-2 is shown in the diagram.
[0036] Figure 9 The diagram shows the liquid absorption rate of the silk fibroin hemostatic sponges prepared in Examples 1-3 and Comparative Examples 1-3.
[0037] Figure 10 The degradation curve of the prepared silk fibroin hemostatic sponge in type I collagenase.
[0038] Figure 11 Polyacrylamide gel electrophoresis image of the degradation products of the prepared silk fibroin hemostatic sponge in type I collagenase; where 1 refers to Example 1, 2 refers to Example 5, and 3 refers to Example 8.
[0039] Figure 12 A comparison of in vitro hemostasis rates between commercially available gelatin sponge and the silk fibroin hemostatic sponge prepared in Example 1.
[0040] Figure 13 The image shows the in vivo degradation of the silk fibroin hemostatic sponges prepared in Example 1, Comparative Example 1, and Comparative Example 3. Detailed Implementation
[0041] The embodiments of the technical solution of the present invention will now be described in detail with reference to the accompanying drawings. These embodiments are merely illustrative of the technical solution of the present invention and are therefore intended to limit the scope of protection of the present invention.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the invention, are intended to cover non-exclusive inclusion.
[0043] In existing technologies, organic solvents are generally used to induce the silk fibroin structure to transform into a silk II structure, enabling it to remain stable in water. However, the resulting hemostatic sponge has a degradation period of more than 30 days, which is long, and may require postoperative removal.
[0044] This invention provides a method for preparing absorbable silk fibroin medical hemostatic sponge, comprising the following steps:
[0045] S1, the first molecular weight silk fibroin solution and the second molecular weight silk fibroin solution are mixed in proportion and then frozen;
[0046] The weight-average molecular weight of the first molecular weight silk fibroin solution is 250-500 kDa, and the weight-average molecular weight of the second molecular weight silk fibroin solution is 50-200 kDa.
[0047] The volume ratio of the first molecular weight silk fibroin solution to the second molecular weight silk fibroin solution is (1-4):1.
[0048] In this invention, the material prepared using a first molecular weight silk fibroin solution has a slower degradation rate, while the material prepared using a second molecular weight silk fibroin solution has a faster degradation rate. Adding a second molecular weight silk fibroin solution to the first molecular weight silk fibroin solution imparts a rapidly degradable property to the hemostatic sponge.
[0049] The mass fractions of the first and second molecular weight silk fibroin solutions were both 4–8 wt%. Experiments showed that when the mass fraction of the silk fibroin solution was 2 wt%, the concentration was too low, resulting in poor mechanical properties of the prepared silk fibroin hemostatic sponge; when the mass fraction of the silk fibroin solution was higher than 8 wt%, the concentration was too high, resulting in excessively high dry strength of the prepared silk fibroin hemostatic sponge, which was not conducive to practical applications.
[0050] The freezing temperature is -10℃ to -196℃. Preferably, the freezing temperature is -40℃ to -80℃.
[0051] It should be noted that, unless otherwise specified, the solution freezing temperature in the following embodiments of the present invention is -40°C.
[0052] S2, the frozen sample obtained in step S1 is placed under conditions higher than freezing temperature but lower than 0°C for heating and aging treatment, so that the silk fibroin structure is transformed into a stable silk I structure; then the obtained frozen body is freeze-dried to obtain absorbable silk fibroin medical hemostatic sponge.
[0053] The temperature for the heating and aging process is -15℃ to 0℃, excluding 0℃. The heating and aging process lasts for 12 hours to 96 hours.
[0054] Freeze-drying refers to vacuum drying at -50℃ for 35-72 hours.
[0055] The absorbable silk fibroin medical hemostatic sponge prepared by the above method can be autonomously and rapidly absorbed in the body, and the hemostatic sponge degrades in the body within 1 week.
[0056] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0057] Example 1
[0058] Please see Figure 1-2 As shown, this embodiment provides a method for preparing absorbable silk fibroin medical hemostatic sponge, including the following steps:
[0059] S1, adjust the mass fraction of silk fibroin solutions with weight-average molecular weights of 338.634 kDa (high molecular weight) and 70.349 kDa (low molecular weight) to 4 wt%, respectively, and blend them according to a volume ratio of 6:4 between the high molecular weight silk fibroin solution (first molecular weight silk fibroin solution) and the low molecular weight silk fibroin solution (second molecular weight silk fibroin solution). Pour the well-mixed solution into a mold and place it at -40°C until the solution is completely frozen.
[0060] S2, the frozen solution is transferred to a -4°C refrigerator for aging treatment for 48 hours to transform the crystal structure of silk fibroin and form a stable silk I structure; then, the obtained frozen silk fibroin body is vacuum dried at -50°C to obtain absorbable silk fibroin medical hemostatic sponge.
[0061] Figure 1 This is a GPC image of the silk fibroin solution used in Example 1.
[0062] "Standard sample" refers to a mixture of protein standards used for calibration and performance testing of gel permeation chromatography (GPC) systems. This standard sample is used to establish a molecular weight-retention time calibration curve, thereby calculating the molecular weight and molecular weight distribution of the sample to be tested based on its retention time.
[0063] Specifically, the standard sample used in this embodiment of the invention is a protein standard mixture (molecular weight range 0.137 kDa-670 kDa) manufactured by Supelco. This protein standard mixture is a lyophilized mixture, and its components include: thyroglobulin (molecular weight approximately 670 kDa), γ-globulin (approximately 150 kDa), ovalbumin (approximately 44.3 kDa), ribonuclease A (approximately 13.7 kDa), and para-aminobenzoic acid (approximately 137 Da). In GPC testing, this protein standard mixture is dissolved in the mobile phase and injected. The retention time of each component is recorded, thus obtaining the calibration relationship between the logarithm of molecular weight and retention time, thereby enabling molecular weight analysis of unknown samples.
[0064] As can be seen, the silk fibroin solution used in this invention has different molecular weights.
[0065] Figure 2 The image shows a scanning electron microscope (SEM) image of the absorbable silk fibroin medical hemostatic sponge prepared in Example 1. As can be seen, the silk fibroin hemostatic sponge has a uniform, interconnected porous structure, which is beneficial for liquid absorption, thus playing an advantage in stopping acute massive bleeding.
[0066] Example 2
[0067] The difference from Example 1 is that the volume ratio of the first molecular weight silk fibroin solution to the second molecular weight silk fibroin solution is 8:2. The rest is roughly the same as in Example 1 and will not be repeated here.
[0068] Example 3
[0069] The difference from Example 1 is that the volume ratio of the first molecular weight silk fibroin solution to the second molecular weight silk fibroin solution is 1:1. The rest is roughly the same as in Example 1 and will not be repeated here.
[0070] Comparative Example 1
[0071] Compared with Example 1, the difference is that the second molecular weight silk fibroin solution was not used, that is, the proportion of the second molecular weight silk fibroin solution was 0. Otherwise, it is roughly the same as Example 1, and will not be repeated here.
[0072] Figure 3 The image shows a scanning electron microscope (SEM) image of the silk fibroin hemostatic sponge prepared in Comparative Example 1. It can be seen that the hemostatic sponge has a porous structure, which facilitates liquid absorption.
[0073] Comparative Example 2
[0074] Compared with Example 1, the difference is that the first molecular weight silk fibroin solution was not used, that is, the proportion of the first molecular weight silk fibroin solution was 0. Otherwise, it is roughly the same as Example 1, and will not be repeated here.
[0075] Figure 4 The image shows a scanning electron microscope (SEM) image of the silk fibroin hemostatic sponge prepared in Comparative Example 2. It can be seen that the hemostatic sponge has a porous structure, but due to the low molecular weight of silk fibroin and its poor mechanical properties, some pore walls collapse, which is detrimental to hemostasis in practical applications.
[0076] Comparative Example 3
[0077] Comparative Example 3 provides a conventional method for preparing porous silk fibroin sponges, comprising the following steps:
[0078] A1. After adjusting the mass fraction of the first molecular weight silk fibroin solution (weight average molecular weight of 338.634 kDa) to 4 wt%, place it in -40℃ until the solution is completely frozen, and then freeze-dry the frozen solution further.
[0079] A2. The freeze-dried sample was soaked in 75% ethanol solution for 2 hours. Then, the ethanol solution was washed with deionized water and the sample was frozen again at -40°C to transform the crystal structure of silk fibroin and form a stable silk II structure. The prepared frozen silk fibroin body was then freeze-dried again to obtain a porous silk fibroin sponge.
[0080] Figure 5 The image shows a scanning electron microscope (SEM) image of the silk fibroin hemostatic sponge prepared in Comparative Example 3. It can be seen that the hemostatic sponge has a porous structure. However, after ethanol treatment, the pore size decreases, which is detrimental to liquid absorption.
[0081] XRD tests were performed on the silk fibroin hemostatic sponges prepared in Example 1 and Comparative Examples 1-3. The test results are as follows: Figure 6 As shown. It should be noted that the tests show that the XRD test results of Comparative Examples 1-2 are the same as those of Example 1. To avoid duplication, Figure 6 Only the XRD test results of Example 1 are shown in the figure.
[0082] Depend on Figure 6 It can be seen that the silk fibroin hemostatic materials prepared in Example 1 and Comparative Examples 1-2 all have a silk I structure, indicating that changes in molecular weight do not affect the crystal structure of the material.
[0083] The silk fibroin hemostatic material prepared in Comparative Example 3 has a silk II structure. This demonstrates that ethanol treatment alters the material's structure and imparts water stability.
[0084] Figure 7 Optical images of the silk fibroin hemostatic sponges prepared in Examples 1-3 and Comparative Examples 1-2. Experiments show that as the proportion of the second molecular weight silk fibroin solution increases, the macroscopic morphology of the hemostatic sponge gradually deteriorates until it collapses and can no longer maintain its shape.
[0085] Specifically, the hemostatic sponge made using only a second molecular weight silk fibroin solution (Comparative Example 2) had poor formability.
[0086] The mechanical properties of the silk fibroin hemostatic sponges prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the test results are as follows: Figure 8 As shown.
[0087] As can be seen, with the increase of the proportion of the second molecular weight silk fibroin solution, the dry mechanical properties of the silk I silk fibroin hemostatic sponge gradually decreased from 465.01 kPa to 93.77 kPa. The compressive stresses of Examples 1-3 were 278.72 kPa, 367.91 kPa, and 144.63 kPa, respectively, which are sufficient for practical applications. However, the compressive stress of Comparative Example 2 was 93.77 kPa; the excessively low stress may affect its application in hemostasis.
[0088] The liquid absorption rate of the silk fibroin hemostatic sponges prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are as follows: Figure 9 As shown.
[0089] Depend on Figure 9 It can be seen that the hemostatic sponge with the silk I structure has a greater liquid absorption rate than the silk II hemostatic sponge. Furthermore, as the proportion of the second molecular weight silk fibroin solution increases, the liquid absorption rate of the silk I silk fibroin hemostatic sponge gradually increases, and the blood absorption time decreases from 135 seconds to 79 seconds. In contrast, the silk II hemostatic sponge prepared in Comparative Example 3 has a longer blood absorption time (210 seconds) due to its smaller pore size, which is not conducive to practical applications.
[0090] When the volume ratio of the first molecular weight silk fibroin solution to the second molecular weight silk fibroin solution is 50:50 (Example 3), the absorption rate is not significantly different from that of Example 1 (the volume ratio of the first molecular weight silk fibroin solution to the second molecular weight silk fibroin solution is 60:40) (110 seconds in Example 1 and 104 seconds in Example 3). Considering mechanical properties, a volume ratio of 60:40 is preferred.
[0091] Examples 4-9 and Comparative Examples 4-7
[0092] Compared with Example 1, the difference is that the mass fraction of the silk fibroin solution and the volume ratio of the first molecular weight silk fibroin solution to the second molecular weight silk fibroin solution were changed. Otherwise, they are roughly the same as in Example 1 and will not be repeated here.
[0093] Example 4 6 wt% 8:2 Example 5 6 wt% 6:4 Example 6 6 wt% 1:1 Example 7 8 wt% 8:2 Example 8 8 wt% 6:4 Example 9 8 wt% 1:1 Comparative Example 4 2 wt% 8:2 Comparative Example 5 2 wt% 6:4 Comparative Example 6 2 wt% 1:1 Comparative Example 7 10 wt% 6:4
[0094] Experiments show that when the mass fraction of the silk fibroin solution is 2 wt% (Comparative Examples 4-6), the mechanical properties of the prepared silk fibroin hemostatic sponge are too poor due to the low mass fraction of the silk fibroin solution, making it unsuitable for normal use in practical applications. When the mass fraction of the silk fibroin solution is 10 wt% (Comparative Example 7), the dry strength of the prepared silk fibroin hemostatic sponge is too high due to the high mass fraction of the silk fibroin solution, making it unsuitable for use in practical applications.
[0095] The in vitro degradation of the prepared silk fibroin hemostatic sponge was tested. The specific process is as follows:
[0096] The initial weight of the prepared silk fibroin hemostatic sponge sample was accurately weighed. It was then placed in 0.01 M PBS solution (containing 1 U / mL type I collagenase, bath ratio 1:200) and incubated in a shaker at 37°C. At specified time points (i.e., days 1, 3, 5, 10, and 21), the sample was thoroughly rinsed with deionized water and dried at 105°C to constant weight.
[0097] The degradation rate is expressed as a percentage of weight loss relative to the initial dry weight. The degradation solution was collected at specified time points, and the degradation products were analyzed using polyacrylamide gel electrophoresis. The results are as follows: Figure 10 , Figure 11 As shown.
[0098] Figure 10 The degradation curve of silk fibroin hemostatic sponge in type I collagenase is shown.
[0099] Figure 11 Polyacrylamide gel electrophoresis image of the degradation products of silk fibroin hemostatic sponge in type I collagenase.
[0100] Depend on Figure 10 It can be seen that the degradation rate of silk I fibroin hemostatic sponge is much higher than that of silk II fibroin hemostatic sponge (Comparative Example 3). The silk II fibroin hemostatic sponge prepared in Comparative Example 3 only degraded by 16.09% after 21 days.
[0101] Furthermore, based on the test results of Example 1 and Comparative Examples 1-2, it can be seen that the silk I silk fibroin hemostatic sponge with a higher proportion of second molecular weight silk fibroin solution exhibits a faster degradation rate. The silk fibroin hemostatic sponge prepared in Comparative Example 1 degraded by 67.52% after 21 days, the silk fibroin hemostatic sponge prepared in Example 1 degraded by 75.75% after 21 days, and the silk fibroin hemostatic sponge prepared in Comparative Example 2 degraded by 87.33% after 21 days.
[0102] Depend on Figure 11 It is known that the degradation products of silk fibroin hemostatic sponge are polypeptides and amino acids, which can be absorbed by the human body.
[0103] Hemostasis experiments were conducted on the prepared silk fibroin hemostatic sponge.
[0104] The specific process is as follows:
[0105] After weighing the animals, anesthesia was administered via a marginal ear vein with 3% sodium pentobarbital (1 mL / kg). A 5 cm incision was made along the midline of the abdomen to gently expose the left lobe of the liver. A standard circular incision was created on the liver surface using a pre-defined circular biopsy puncture device. Immediately, a piece of silk fibroin hemostatic sponge prepared in Example 1 was placed over the wound, and gentle pressure was applied with dry gauze. Hemostasis was observed every 20 seconds, and the test results were as follows: Figure 12 As shown.
[0106] Depend on Figure 12 It can be seen that, compared with the gelatin hemostatic sponge (Hushida®, 89 seconds), the silk fibroin hemostatic sponge prepared in Example 1 has a faster hemostatic speed (59 seconds).
[0107] In vivo degradation experiments were conducted on the silk fibroin hemostatic sponges prepared in Example 1, Comparative Example 1, and Comparative Example 3. The specific procedures are as follows:
[0108] After weighing the animals, they were anesthetized by injecting 3% sodium pentobarbital (1 mL / kg) into the marginal ear vein. The samples were weighed and placed subcutaneously in the animals and removed 4 days later.
[0109] like Figure 13 As shown, after four days of degradation, Example 1 and Comparative Example 1 exhibited a faster degradation rate compared to Comparative Example 3.
[0110] Comparing Example 1 and Comparative Example 1, it can be seen that Example 1 has a faster degradation rate, and the silk fibroin hemostatic sponge could not maintain its shape in vivo after four days. Therefore, the silk fibroin hemostatic sponge prepared by this invention can be autonomously and rapidly absorbed in vivo, achieving degradation within one week.
[0111] It should be noted that the present invention is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments that have the same structure and perform the same effects as the technical concept within the scope of the present invention are included within the scope of the present invention. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of the present invention, are also included within the scope of the present invention.
Claims
1. A method for preparing an absorbable silk fibroin medical hemostatic sponge, characterized in that, Includes the following steps: S1, a first molecular weight silk fibroin solution and a second molecular weight silk fibroin solution are mixed at a volume ratio of (1-4):1, and then frozen; wherein the weight-average molecular weight of the first molecular weight silk fibroin solution is 250-500 kDa, and the weight-average molecular weight of the second molecular weight silk fibroin solution is 50-200 kDa; the mass fraction of both the first molecular weight silk fibroin solution and the second molecular weight silk fibroin solution is 4-8 wt%. S2, the frozen sample obtained in step S1 is placed under conditions higher than freezing temperature but lower than 0°C for heating and aging treatment, so that the silk fibroin structure is transformed into a stable silk I structure; then the obtained frozen body is freeze-dried to obtain absorbable silk fibroin medical hemostatic sponge.
2. The method for preparing absorbable silk fibroin medical hemostatic sponge according to claim 1, characterized in that, In step S2, the temperature for the heating and aging process is -15℃ to 0℃, excluding 0℃.
3. The method for preparing absorbable silk fibroin medical hemostatic sponge according to claim 1, characterized in that, In step S2, the heating and aging process takes 12-96 hours.
4. The method for preparing absorbable silk fibroin medical hemostatic sponge according to claim 1, characterized in that, In step S1, the freezing temperature is -10℃ ~ -196℃.
5. The method for preparing absorbable silk fibroin medical hemostatic sponge according to claim 1, characterized in that, In step S1, the freezing temperature is -40℃ to -80℃.
6. The method for preparing absorbable silk fibroin medical hemostatic sponge according to claim 1, characterized in that, The freeze-drying refers to vacuum drying at -50℃ for 35-72 hours.
7. An absorbable silk fibroin medical hemostatic sponge, characterized in that, The absorbable silk fibroin medical hemostatic sponge is prepared by the preparation method described in any one of claims 1-6; the absorbable silk fibroin medical hemostatic sponge is a hemostatic sponge with a silk I structure.
Citation Information
Patent Citations
Preparation method of hemostatic sponge and hemostatic sponge prepared thereby
CN109091699A
Silk fibroin hemostatic sponge loaded with polyhydroxy phenolic compound and preparation method of silk fibroin hemostatic sponge
CN120285272A
